Efisiensi Fiskal Terhadap Pembangunan Ekonomi Propinsi di Pulau Jawa (Tahun 2005-2009) - Diana Wijayanti; Ai Susan (Jurnal Aplikasi Bisnis, 2017)
The study was conducted to determine the extent to which fiscal policy can affect the efficiency of the economic development of each province on the island of Java. Data in this study sourced from a central lureau of statistics. Each province has different characteristics from one another. The difference of these characteristics is seen from the inputs used by each province of the output produced. This can he measured by using Indirect Expenditure report, Expenditures and direct Local Spending source as input variables. GDP or the rate of economic growth and employment as an output variable.Analysis tools used in this study is the efficient measurement model with technique Data Envelopment Analysis (DEA). DBA is a Technique that compares linear programming of various inputs and output of each unit of economic activity (UKE).This study concluded that: (1) Province in Java that can reach and be able to maintain a level of efficienty of 100% from the year 2005-2009 only one province of East Java Province, while the Province of DKI Jakarta, West Java, Central Java, Yogyakarta and Bantam efficieniy level fluctuate each year. (2) Provinces that have a value of inefficient or <100%, occurred because the thriftless in the province of using the input.